Self‐Piercing Riveting of Hot Stamped Steel and Aluminum Alloy Sheets Base on Local Softening Zone. Issue 4 (9th December 2020) - Zhang, Yongqiang; Yi, Rigui; Wang, Pengbo; Fu, Can; Cai, Ning; Ju, Jianbin
Abstract : Self‐piercing riveting (SPR) has been used to joint steel to aluminum alloy sheets in multimaterial car body. It is a challenge to joint high strength steel to aluminum alloy by SPR process, especially for materials with high strength and large thickness. Herein, the SPR process for 1500 MPa hot stamped steel and aluminum alloy sheets is studied by experiment and simulation method. The laser heat treatment process is applied to the hot stamped steel sheet before joining. The relationship between heat treatment process and hardness distribution is studied and the softening zone with hardness less than 300 HV is obtained. Furthermore, the local softening zone is joined to an aluminum alloy sheet by SPR process. In the process, the rivets with high hardness are used to pierce the steel sheet. The failure mode and maximum tensile shear force of the joint are studied. At the same time, the joints without laser heat treatment are compared. The results show that the interlock and the maximum shear force for laser heat treatment increase by 91% and 26%, respectively. Abstract : Self‐piercing riveting (SPR) process for 22MnB5 and aluminum alloy sheets is studied. The laser heat treatment is applied to 22MnB5 before joining. The softening zone with hardness less than 300 HV is obtained, and it is joined to aluminum alloy by SPR process. The joint interlock and the maximum shear force for laser treatment increase by 91% and 26%, respectively.